Vivian Yeaman. The Restoration of the Old Republic: The End of Communism in Latvia - Yeaman, Vivian (Young Scholars Grinchenko – Seton International Journal, 2022)
Three factors that contributed to the fall of the Latvian SSR were Gorbachev’s glasnost and perestroika policies, the ethnonationalist movements that arose in response to decades of Russification, and the failure of the USSR to respond to the independence movements in Latvia. Gorbachev’s reforms accelerated a discontent among the Latvian people that had been growing for years, and the response of force by the USSR to largely nonviolent protests gained the protester's notoriety and sympathy in the West. Had the Latvian SSR not been as lenient with their policies on free expression, it likely would have taken longer for these protests to gain traction, and if the USSR had not taken a strong approach to Russification in Latvia, the ethnonationalist movements might not have been as successful among the Latvian population. All this contributed to Latvia successfully declaring independence in 1991 after a coup in the USSR failed to remove Gorbachev from power.